Change management toolkit : a step-by-step methodology for successfully implementing dramatic organizational change. - Skarke, Gary....[et al.] (WinHope P. HoustonUS, 1995)
Defines reengineering. Presents a practical change management approach to applying reengineering in an organization, in 4 phases viz.: position for change; diagnose the existing process; redesign the process; and, transition to the new design. Provides step-by-step methodology, lists activities, and outlines the techniques/tools needed to accomplish each step.